STRUCTURE AND FUNCTIONS OF FAMILY NARRATIVE IN THE NOVEL BY KATE ATKINSON «BEHIND THE SCENES AT THE MUSEUM» - Likhomanova, Natalia (Літературний процес: методологія, імена, тенденції, 2019)
DOI: 10.28925/2412-2475.2019.1411 The article deals with the issues of functioning and structure of the family narrative in the contemporary literary process. The relevance of the topic is demonstrated by the limited number of literary studies that are more focused on the study of particular types of narratives, including family narratives. These are separate genre articles that define the family narrative primarily as the formative basis of the family novel.On the example of the novel by contemporary English writer Kate Atkinson “Behind the Scenes at the Museum”, the structure of the family narrative is analyzed. The tradition of first-person narration («Self»-narration) is preserved, demonstrating an example of the detailed functioning of the homodiegetic type of narrator in the text. The family history narrator is both a direct participant in the events, an observer, and a collector of collective memory. One element of the narrative structure of K. Atkinson’s artistic space is the traditional cyclicality for the family narrative: the story of a disappearing woman / mother, the story of family vacations, travel to exotic countries, and more.The peculiarities of the embodiment of narrative metalepsis (J. Jeanette) are defined as a narrative play with the reader, which is a characteristic feature of the family narrative. The narrative reverse is analyzed, which is demonstrated in the penetration of two incompatible spatio-temporal worlds with each other in the presence of story logic and completeness of the story. In the narrative metalepsis of the novel “Behind the Scenes at the Museum” «female narrative privileges» prevail. The narrator cyclically changes from homodiegetic to heterodiegetic, but the narrator’s attention is always focused on the female images.